SQUEEZE CEMENTING PLANNING USING BALANCE PLUG METHOD IN LOSS FORMATION ON “TBN-10” - Prasetyo, Wahyu; Yunita, Lia (KURVATEK, 2025)
The TBN-10 well in the subang field is a production well that has experienced a decline in productivity, so it was decided to close the perforation zone in layer 9C using the squeeze cementing method and open a new perforation in layer 9D. This work faces challenges in the form of a loss circulation zone in the baturaja formation, so it is necessary to plan the appropriate cement method and composition. The squeeze cementing method is carried out using the balance plug method, accompanied by the selection of class G cement and special additives such as BAF-14L, BAR-19L, BAL-22L, BAG-17L, and BAF-26L to overcome high pressure conditions, high temperatures, and potential gas disturbances and fluid loss. The calculation of slurry volume, water head, water behind, displacement, and slurry specifications was carried out in detail resulting in a slurry requirement of 15.10 bbl. Laboratory test results showed a thickening time value of 4 hours 29 minutes at a consistency of 100 Bc and a compressive strength of 623 psi in 24 hours. Field evaluation showed that the cementing work successfully formed good isolation on the old perforation zone and allowed the opening of a new, more productive zone. This work successfully repaired the well integrity and became the basis for a workover strategy with a target of significantly increasing production from more economical layers.